Bridging Microeconomics and Macroeconomics and the Effects on Economic Development and Growth - Kostis, Pantelis C. (IGI Global, 2020)
At the eve of the global financial crisis, it is particularly interesting to find out which are the theoretical bases or theoretical models that we can use to analyze today's reality. Indeed, today’s mainstream micro- and macroeconomic models are proven to be insufficient for exploring the dynamic and complex interactions among humans, institutions, and nature in our real economy. This issue has again gained momentum because of the recent global financial crisis, as theoretical constructs or models have been unable to provide interpretations of what really happened and what has to be done from now on. More precisely it is proven that microeconomics is filled with black-box models that fail to study the actual contractual relations between firms and markets, while macroeconomics over the last three decades has been useless at best and harmful at worst, since economists using macroeconomics became blind to catastrophic macro failure because they mistook the beauty or elegance of theoretical models for truth. Thus, questions have arisen about using new theoretical and empirical structures that would better describe our complex economic systems.  This edited book aims to address issues related to how growth issues are treated as having individual origins, but also how aggregates affect parts of the economic system with the ultimate goal of highlighting important microeconomic factors that affect macroeconomic factors and finally the economic development and growth process. This is the question of whether and how theoretical constructs take account of the application of microeconomic approaches to macroeconomic theory and how economies can be driven to a sustainable economic development and growth path. Thus, the scope is to analyze the hypotheses that govern the relationships of aggregate structures (macroeconomic analysis) that may are compatible with the assumptions that govern the behavior of the individuals, households, and firms (micro analysis), and vice versa, in trying to achieve positive economic growth rates, sustainably. Moreover, the analysis of this edited volume is oriented to focus on deeper issues that affect the functioning of the economic systems; this is what mesoeconomics and metaeconomics analysis deals with, since the focus must be in factors that are the deep roots of economic development and growth that bridge the microeconomics to macroeconomics. This is the future of evolutionary growth thinking over the next decades.